Morbimortalidade por causas externas em idosos atendidos em hospital de emergência e trauma - Lavôr, Rogéria Máximo de (2015)
Introduction: The set of health disorders defined as external causes is categorized into unintentional called accidental and intentional, called violence. The routine of the elderly population is increasingly active, increasing the chances of occurrence of injuries from external causes. Objective: To identify morbidity and mortality from external causes in older adults admitted in a public Emergency and Trauma hospital of João Pessoa, Paraíba. Material and methods: Cross-sectional study through the analysis of 621 medical records of patients aged over 60 years hospitalized due to external causes from January to December 2011. The survey instrument consisted of a specific form developed from the analysis of medical records. The variables used were gender, age, marital status, time of occurrence, occurrence over the weekend, etiology, type of fall, presence of fracture, presence of femur fracture, site of femur fracture, Traumatic brain injury (TBI), and death. Data were analyzed using SPSS (Statistical Package for Social Sciences) version 18, also using the Pearson's chi-square and Fisher's exact tests, considering the statistical significance value (p <0.05). Results: There was predominance of female victims (51.2%) and age group of 60-69 years, accounting for 38% of cases. The main causes of morbidity and mortality were falls and traffic accidents (68.6% and 18.8%, respectively). Fractures were more common in females aged 80 years and over and cases of TBI were more prevalent in males in the age group of 60 -69 years. The main cause of death was fall (69.9%) in males aged 80 years or more. Significant associations were observed (p <0.001) among variables "gender," "etiology", "presence of fractures", "TBI" according to "age group". As for hospital admissions due to fall, there was predominance of females (62.4%) aged 80 years and over (41.6%), and the most frequent fractures were those involving femur (57%); presence of TBI was observed in 14.3% of cases and the highest proportions of deaths occurred in the age group of 80 years and over (21.8%). Conclusion: Falls and traffic accidents were the most prevalent causes of morbidity and mortality from external causes, female gender and age group of 60-79 years were predominant and falls were the main cause. These data are useful for the development of preventive measures and hospital care based on potential demand, providing better quality of life for this specific population and reducing spending for rehabilitation.